Recombinase polymerase amplification (RPA) with lateral flow detection for three Anaplasma species of importance to livestock health - Andrea Salazar (Nature Portfolio, 2021)
Abstract Anaplasma marginale, A. ovis, and A. phagocytophilum are the causative agents of bovine anaplasmosis, ovine anaplasmosis, and granulocytic anaplasmosis, respectively. The gold standard for diagnosis of post-acute and long-term persistent infections is the serological cELISA, which does not discriminate between Anaplasma species and requires highly equipped laboratories and trained personnel. This study addresses the development of a rapid, isothermal, sensitive, species-specific RPA assays to detect three Anaplasma species in blood and cELISA A. marginale-positive serum samples. Three RPA primer and probe sets were designed targeting msp4 genes of each Anaplasma species and the internal control (GAPDH gene) for each assay. The limit of detection of gel-based or RPA-basic assays is 8.99 × 104 copies/µl = A. marginale, 5.04 × 106 copies/µl = A. ovis, and 4.58 × 103 copies/µl = A. phagocytophilum, and for each multiplex lateral flow or RPA-nfo assays is 8.99 × 103 copies/µl of A. marginale, 5.04 × 103 copies/µl of A. ovis, 4.58 × 103 copies/µl of A. phagocytophilum, and 5.51 × 103 copies/µl of internal control (GAPDH). Although none of the 80 blood samples collected from Oklahoma cattle were positive, the RPA-nfo assays detected all A. marginale cattle blood samples with varying prevalence rates of infection, 83% of the 24 cELISA A. marginale-positive serum samples, and all A. phagocytophilum cell culture samples. Overall, although early detection of three Anaplasma species was not specifically addressed, the described RPA technique represents an improvement for detection of three Anaplasma in regions where access to laboratory equipment is limited.